PENGARUH KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BANK MANDIRI (PERSERO) Tbk, AREA MANADO - SAID, MEGAWATI; Rumawas, Wilhelmina; Asaloei, Sandra Ingrid (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
The continuity of the organization or company is determined by the existinghuman resources, both quality and quantity. Each organization has differentobjectives and in the implementation is done by employees. Employees are thereforea major factor in corporate activities. Each organization will basically have differentpolicies on the human resources it has to achieve employee productivity. In theachievement that affects the productivity of employees there are many factors thataffect work productivity, among others, is the existence of job satisfaction. With asense of satisfaction in working the employee will show a good personal in thecompany, a positive performance that satisfies the company and arises willingness towork high level of work productivity for the interests of the company, and facilitatethe achievement of corporate goals. Job satisfaction is an evaluation that describes aperson for feeling his attitude, happy or not happy, satisfied or not satisfied in workThe purpose of this study is to analyze the effect of job satisfaction on employeeproductivity at PT. Bank Mandiri (Persero) Tbk, Area Manado. Job Satisfaction ismeasured through five indicators, namely Jobs, rewards, supervision of superiors,co-workers, and promotional opportunities. This research is a quantitative researchby using simple linear regression approach. Data collection techniques were done bydistributing questionnaires filled by 39 respondents and analyzed using simpleregression analysis and using test t test hypothesis. From the results of simple linearregression analysis of job satisfaction variables affect the productivity of employeesof PT. Bank Mandiri (Persero) Tbk, Area Manado. And result of hypothesis test showthat job satisfaction variable simultaneously have a significant effect to workproductivity of PT. Bank Mandiri (Persero) Tbk, Area Manado. Based on the resultsof this study, the company can continue to facilitate employees in improving jobsatisfaction so that employee productivity can be achieved..Keywords: Job Satisfaction, Work Productivity.